Penerapan Model Pembelajaran Jigsaw Sebagai Sarana Untuk Problem Solving Bagi Mahasiswa Pada Mata Kuliah Ilmu Pendidikan - Anita Afrianingsih (At-Tarbawi: Jurnal Kajian Kependidikan Islam, 2019)
AbstrakThe objectives of this study are: 1) to know the implementation of the Jigsaw learning model that is used as a means for problem solving for students in educational science courses, 2) To measure the success rate of implementing the Jigsaw learning model that is used as a means for problem solving education science courses, 3) To find out student responses related to the implementation of the Jigsaw learning model that is used as a means for problem solving for students in educational science courses. This research method applies an experimental method with a type of non-equivalent control group design in answering the research problem formulation. The research location was at the Nahdlatul Ulama Islamic University of Jepara, with a population of 30 students. Data analysis techniques used to calculate the results of research using t-test (paired sample t-test and independent sample t-test). Instruments for collecting data using observation and questionnaires.The results of this study include: 1) the continued impact of this is a different level of understanding between active students and students who are passive in completing tasks / problems. active students will of course be better able to master the material, whereas students who are passive will find it difficult to carry out the material by using learning models like this (problem solving). This is indicated by the value of learning outcomes, observation sheet data problem solving process shows that 71% of students in meetings II and II, and 76% of students at meetings IV and V can attend learning well; 2) Based on the statistical data generated, it can be concluded that the initial capability data of the 3 classes of 2PGSD A.1 has identical means (not significantly different) because Sig. (0.232)> 0.05, and F count (1.479) < T table (3,072); and 3) students taught by using the Jigsaw learning model that is used as a means for problem solving for students in Educational Sciences courses can be setup cooperatively to provide higher learning outcomes compared to students taught with classical learning models as a means for problem solving that is set individually. This proves that the Jigsaw learning model through problem solving activities can provide strength that is able to support the improvement of learning outcomes and critical thinking skills and build an active role for student learning.Â